Engineering Escherichia coli FAB system using synthetic plant genes for the production of long chain fatty acids - Elias Kassab; Monika Fuchs; Martina Haack; Norbert Mehlmer; Thomas B. Brueck (Microbial Cell Factories, 2019)
Abstract Background Sustainable production of microbial fatty acids derivatives has the potential to replace petroleum based equivalents in the chemical, cosmetic and pharmaceutical industry. Most fatty acid sources for production oleochemicals are currently plant derived. However, utilization of these crops are associated with land use change and food competition. Microbial oils could be an alternative source of fatty acids, which circumvents the issue with agricultural competition. Results In this study, we generated a chimeric microbial production system that features aspects of both prokaryotic and eukaryotic fatty acid biosynthetic pathways targeted towards the generation of long chain fatty acids. We redirected the type-II fatty acid biosynthetic pathway of Escherichia coli BL21 (DE3) strain by incorporating two homologues of the beta-ketoacyl-[acyl carrier protein] synthase I and II from the chloroplastic fatty acid biosynthetic pathway of Arabidopsis thaliana. The microbial clones harboring the heterologous pathway yielded 292 mg/g and 220 mg/g DCW for KAS I and KAS II harboring plasmids respectively. Surprisingly, beta-ketoacyl synthases KASI/II isolated from A. thaliana showed compatibility with the FAB pathway in E. coli. Conclusion The efficiency of the heterologous plant enzymes supersedes the overexpression of the native enzyme in the E. coli production system, which leads to cell death in fabF overexpression and fabB deletion mutants. The utilization of our plasmid based system would allow generation of plant like fatty acids in E. coli and their subsequent chemical or enzymatic conversion to high end oleochemical products.